USO DE ESPECTROSCOPÍA INFRARROJA CON TRANSFORMADA DE FOURIER Y pH ENEL ESTUDIO DE CONGLOMERANTES PARA MORTEROS MIXTOS - Yurany Andrea Hoyos Tejada; Ligia María Vélez Moreno (IJRDO-Journal of Applied Science, 2019)
This work presents the advances of research in conglomerates for mixed mortars, an important search of new and modified conglomerating materials is developed for its use in works of restoration of the Cultural Heritage, taking into account an experimental methodology, with four main conglomerates (Portland gray cement) , fat lime, hydroxyapatite and gypsum plaster); which were subjected to tests of specific gravity, infrared spectroscopy (IR) and pH measurement to evaluate the existence of carbonation; and then compare the results obtained. It is concluded: the mortar with gray cement, has a high concentration of calcium hydroxide, considerable alkalinity is produced, with a pH equal to 12.5. The carbon dioxide, responsible for carbonation, reduces the pH of the mortar, depassivating the steel facilitating the attack of substances. Contrary to the foregoing, in gypsum plaster the peak 455 cm -1 of the IR, leads to the deformation of ferrite in austenite; what is reflected in the solubility of the mixture, which increases the thermal insulation. And also, the functional component of amorphous sulfates achieving greater compactness of the mixed mortar, the pH in the fat lime of 12.74 does not represent acidity and turns the mortar into a durable material.